Efecto de altas densidades y dos sistemas de siembra sobre el rendimiento y rentabilidad del cultivo de plátano (Musa AAB) bajo condiciones de regadío. - Yépez Neira, Juan Carlos (2015)
The Experimental Tropical Pichilingue (EETP) Station, the National Autonomous Institute for Agricultural Research (lNlAP) is located in the province of Los Rios, 5 km route Quevedo - The Junction, the effect of high densities was studied and two planting systems on the performance and profitability of plantain (Musa AAB) under irrigated conditions. The experiment consisted of eight treatments under design split plot with three replicates per treatment, where the main plots were assigned the factor A (System planting a double row and single row) and small plots were assigned the factor B (four densities).